Impaired Kallikrein-Kinin System in COVID-19 Patients' Severity - Enrique Alfaro; Elena Díaz-García; Elena Díaz-García; Sara García-Tovar; Ester Zamarrón; Ester Zamarrón; Alberto Mangas; Raúl Galera; Raúl Galera; Kapil Nanwani-Nanwani; Rebeca Pérez-de-Diego; Rebeca Pérez-de-Diego; et al. (Frontiers in Immunology, 2022)
COVID-19 has emerged as a devastating disease in the last 2 years. Many authors appointed to the importance of kallikrein-kinin system (KKS) in COVID-19 pathophysiology as it is involved in inflammation, vascular homeostasis, and coagulation. We aim to study the bradykinin cascade and its involvement in severity of patients with COVID-19. This is an observational cohort study involving 63 consecutive patients with severe COVID-19 pneumonia and 27 healthy subjects as control group. Clinical laboratory findings and plasma protein concentration of KKS peptides [bradykinin (BK), BK1-8], KKS proteins [high–molecular weight kininogen (HK)], and KKS enzymes [carboxypeptidase N subunit 1 (CPN1), kallikrein B1 (KLKB1), angiotensin converting enzyme 2 (ACE2), and C1 esterase inhibitor (C1INH)] were analyzed. We detected dysregulated KKS in patients with COVID-19, characterized by an accumulation of BK1-8 in combination with decreased levels of BK. Accumulated BK1-8 was related to severity of patients with COVID-19. A multivariate logistic regression model retained BK1-8, BK, and D-dimer as independent predictor factors to intensive care unit (ICU) admission. A Youden’s optimal cutoff value of −0.352 was found for the multivariate model score with an accuracy of 92.9%. Multivariate model score-high group presented an odds ratio for ICU admission of 260.0. BK1-8 was related to inflammation, coagulation, and lymphopenia. Our data suggest that BK1-8/BK plasma concentration in combination with D-dimer levels might be retained as independent predictors for ICU admission in patients with COVID-19. Moreover, we reported KKS dysregulation in patients with COVID-19, which was related to disease severity by means of inflammation, hypercoagulation, and lymphopenia.